Clinical Profile and Ultrasonographic Evaluation of Brain in Perinatal Asphyxia (Bangladesh Medical Journal, 2014)
This descriptive cross sectional study was carried out in the department of paediatrics, Mymensingh Medical College Hospital from March 2006 to December 2006. This study was performed on 100 consecutive asphyxiated newborns who were admitted in Mymensingh Medical College Hospital during the study period. Among them, 50 babies were preterm and 50 babies were full term with moderate to severe perinatal asphyxia. Full term (>37 weeks of gestation) and preterm (